(untitled) (Damascus University Journal of arts and humanities sciences, 2023)
This study aims to analyze the intellectual production published on the website of the Damascus University Journal of the College of Arts and Humanities, in order to know the general characteristics of intellectual production, authorship and reference citations contained in articles due to their importance and the novelty of their information. Where the bibliometric method was used to analyze the articles of the Damascus University Journal of the Faculty of Arts and Humanities contained in 4 years from (2018) to (2021), and the results indicate the quantitative distribution of the articles, which number up to (160) articles published on the site within twelve issues, and to the distribution The timeline of articles, as the year (2021) is the most published for intellectual production, in addition to knowing the most published topics within the Damascus University Journal of the Faculty of Arts and Humanities, which are topics related to the Arabic language, which amounted to (23.75%) out of 14 topics, in addition to knowing the most published authors And the characteristics of citing references contained in periodical articles, whose number reaches (3650), and the percentage of citations for periodicals is (10.90%) and knowing the most cited periodicals, which is the Damascus University Journal with a percentage of (10.24%).